(untitled) (Physical Education, Health and Social Sciences, 2025)
The origin of water pollutants becomes evident when performing chemical water examinations. Water obtains dangerous components that stem either from natural mineral resources or from human-caused agricultural runoff together with industrial waste releases. Deficient water quality assessment methods have led to the selection of poor treatment solutions while causing delays in reacting to water contamination incidents. The paper analyzes water composition using both chemical and bacteriological assessment methods in Peshawar district. The investigation checks for dangerous substances and microbial signs to measure water security levels. Full comprehension regarding pollutants within water enables effective installation of monitoring programs and appropriate treatment procedures. The paper works to combine information from chemical measurements and bacterial evaluations which will strengthen regulatory systems and protect public health. The paper findings will significantly advance water management techniques for improved community health outcomes. This study was conducted in Hayatabad, Peshawar, and adopted a laboratory-based analytical design to assess the quality of drinking water sources in the area. Two water samples were collected from different locations, one from a tubewell and the other from a water storage tank, using sterile plastic bottles to avoid contamination. The samples were properly labeled and transported under controlled conditions to the PCSIR Laboratories Complex, Peshawar, for analysis. The tubewell water sample was subjected to comprehensive chemical analysis, including parameters such as pH, total dissolved solids, hardness, alkalinity, major ions, and conductivity, while the tank water sample was analyzed bacteriologically to determine total plate count, coliform, and fecal coliform bacteria. Standardized laboratory methods were employed to evaluate whether the collected water samples met safety requirements for drinking purposes.